Generation of NOD SCID mice with near-complete deletions of Il2rg and Prkdc for human cancer and HSC engraftment - You-Min Kim; Hee Ju Na; Do Hee Kwon; Jae Hoon Lee; Bo Min Park; Subin Lee; Tae Wook Nam; Mi Yeon Park; Sun Ha Park; Sung Joo Kim; Bongkum Choi; Han-Woong Lee (Transgenic Research, 2025)
Immunodeficient mouse models are invaluable tools for preclinical research, particularly for cancer therapies and studies of the human immune system. Notably, strains with combined Prkdc (scid) and Il2rg (null) mutations—such as NOG and NSG mice— are widely used due to their profound immunodeficiency, allowing efficient engraftment of various human cells. However, these models were generated by disrupting the Il2rg gene through replacement with a neomycin resistance (Neo) cassette in embryonic stem cells. Incomplete excision of this cassette can inadvertently alter the expression of neighboring genes, thereby introducing potential confounding variables. In addition, they may still express mutant mRNAs that escape nonsense-mediated decay (NMD) and/or produce truncated proteins with residual activity, potentially compromising the interpretation of experimental outcomes. To address this, we developed the N2G mouse strain (NOD-2-Genes KO) where almost all genomic loci of both Prkdc and Il2rg genes are deleted via CRISPR/Cas9 genome editing. N2G mice exhibited tumor growth comparable to NOG mice following the transplantation with several human cancer cell lines. Moreover, human CD34 + cord blood (CB) cells engrafted into N2G mice showed robust reconstitution of human immune cells, especially T cells in peripheral blood, spleen and bone marrow, compared to NSG mice. These results suggest that N2G mice, lacking residual mutant mRNA and the exogenous Neo resistant gene, offer an advanced model for preclinical studies.